Respiratory Syncytial Virus Vaccination during Pregnancy and Effects in Infants - Madhi, Shabir A; Polack, Fernando P; Piedra, Pedro A; Munoz, Flor M; Trenholme, Adrian A; Simões, Eric A.F; Swamy, Geeta K; Agrawal, Sapeckshita; Ahmed, Khatija; August, Allison; Baqui, Abdullah H; Calvert, Anna; et al. (The New England journal of medicine, 2020)
This randomized trial of RSV F protein nanoparticle vaccination during pregnancy did not show efficacy (according to the prespecified success criterion) against RSV-associated, medically significant lower respiratory tract infection but suggested possible benefits with respect to other RSV-related outcomes.